Occupational methanol toxicity: a case report study - Alrougi, Hamoud M.; Saqah, Rayyan; Khojah, Imad; Amer, Samar A. (Frontiers in Medicine, 2025)
This case report describes a case of methanol occupational toxicity in a 44 year-old male ship worker in Jeddah, Saudi Arabia, on 27 August 2024. The patient suddenly lost sight in both eyes and had an unusual acid-base disturbance that was marked by respiratory alkalosis (pH 7.607). This is different from the acidosis that is usually seen in methanol poisoning. Despite aggressive treatment with FOMEPIZOLE, the methanol antidote, and four hemodialysis sessions, the patient’s visual prognosis remained poor. This case highlights the potentially devastating consequences of inhalational and contact methanol poisoning and the importance of prompt recognition and treatment, even in the absence of significant neuroimaging findings. It also underscores the need for proper use of personal protective equipment (PPE) in the workplace.